Sustainable Tourism: The Moderating Effect of Tourists’ Educational Background in the Relationship Between Green Practices and Customer Satisfaction - Awang, Zainudin; Yusnita, Y.; Afthanorhan, Asyraf (International Journal of Engineering and Technology, 2018)
The tourism industry is one of the largest and fastest growing economic sectors in the world and has contributed to world economic growth. Since the tourism industry is among those directly related to the environment, green tourism has an important role in the environment management system, especially practices that have the ability to reduce negative impacts onto the environment. Green initiatives are considered part of the programs adopted in many parts of the tourism sector. This article examines the influence of green practices and a green image towards customer satisfaction and customer loyalty. To test the theoretical framework, some 385 data were analysed using Structural Equation Modeling (SEM). Results revealed that green practices have stronger effects on customer satisfaction compared to a green image. The moderation test indicated that touristsâ€™ educational background moderates the relationship between green practices and customer satisfaction, where the effect among tourists with a high education level is higher compared to those with a low education level. Further analysis showed that green practices and a green image lead to customer loyalty indirectly through customer satisfaction. The results present many implications towards theory and practice as far as the tourism industry is concerned.Â Â